(untitled) (Revista Espinhaço, 2021)
The das Velhas river basin has been intensively studied with water quality bioindicators in the last two decades. the objective was to evaluate the ecological quality in the upper das Velhas river (São Bartolomeu, Ouro Preto, MG), using the Rapid Ecological Assessment approach. We seek to answer: (i) Is the water quality of the das Velhas river altered by the release of urban effluents in the District of São Bartolomeu? (ii) Has there been a loss of water quality over time, comparing historical biomonitoring with current conditions? We evaluated three sample sites: P1 (reference), P2 (within the district), P3 (downstream from the Treatment Plant). We used a Rapid Assessment Protocol for Habitat Diversity and Riparian Zone Integrity, measured physical, chemical and bacteriological parameters in the water column and calculated a Water Quality Index. Benthic macroinvertebrates and fish were sampled as bioindicators. Compared to the historical average, there was anincrease in total-N and total-P concentrations and a reduction in total dissolved solids, turbidity and electrical conductivity. e bioindicators showed a loss of environmental quality, a reduction in the diversity index in P2 and P3, a lower percentage of sensitive and tolerant organisms, greater abundance of pollutionresistant organisms. We observed a twenty-fold increase in the concentrations of Escherichia coli bacteria in P2 and P3, evidencing a health risk for riverside populations. We recommend that the efficiency of the Treatment Plant be improved and that no domestic sewage is released into the das Velhas river. We reinforce the importance of conserving the natural streambed, conserving the diversity of habitats and riparian vegetation. We suggest intensifying environmental awareness campaigns, implementing riparian forest reforestation campaigns and carrying out a longterm Biomonitoring Program with Environmental Education and citizen science activities with residents, tourists, teachers, young people and schoolchildren.